The Genus Bryonia : A Review - Kumar, Suresh; Madaan, Reecha; Gahlot, Kavita; Sharma, Anupam (Pharmacognosy Reviews)
The review includes 103 references on the genus Bryonia, and comprises ethnopharmacology, morphology and microscopy, phytoconstituents, pharmacological reports, clinical studies and toxicology of the prominent species of Bryonia. Alkaloids, flavonoids and triterpenoids constitute major classes of phytoconstituents of the genus. A few species of this genus have medicinal value, among these, B. alba Linn. (Cucurbitaceae) has been traditionally used in the treatment of cough, typhoid, pneumonia, inflammation of serous tissues, nervous disorders, rheumatism and jaundice. B. alba has also been included in homoeopathic formulations which are in clinical use for its antirheumatic, antiphlogistic and anti-anxiety activities. Despite a long tradition of use of some species, the genus has not been explored properly. In the concluding part, the future scope of Bryonia species, has been emphasized with a view to establish their multifarious biological activities and mode of action.
Keywords: Alkaloids; Bryonia alba; Flavonoids; Triterpenoids